Using a Direct Multiple Shooting Method to an Optimal control problem Direct Multiple Shooting Method - Lounis, Abbes; Marthon, Philippe; Louadj, Kahina; Aidene, Mohamed (University of Eloued جامعة الوادي, 2022)
A multiple direct fire method is considered to solve optimal control problems. The multiple direct multiple shooting method is a numerical method for solving limit value problems. The method divides the interval over which a solution is sought into several smaller intervals, solves an initial value problem in each of the smaller intervals, and imposes additional matching conditions to form a solution over the entire interval. This method transforms an optimal control problem into a non-linear programming problem. To solve the latter problem, the zeros of the Lagrange Jacobian are computed using Newton’s method. Then, this method is illustrated by a numerical example and finally.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Optimal control · Multiple Shooting Method · Non-Linear Programming Problem · Newton’s method